Hunter Success and Crippling Losses for Bobwhite Quail - Gary L. Doster; Forest E. Kellogg; Gary L. Doster; Ernest E. Provost (National Quail Symposium Proceedings, 2017)
During a two-week period each February from 1972 through 1981, bobwhite quail (Colinus virginianus) were collected on two study sites consisting of 202 and 210 hectares (505 and 524 acres, respectively). Bobwhites were collected by conventional sport hunting techniques, and records were maintained on several criteria concerning hunter success and crippling loss. During the 10-year study, 108 different hunters using 112 different dogs hunted a total of 3,089 man hours, flushed 15, 576 bobwhites, fired 6,820 shots, bagged 2,245 bobwhites, shot down and lost 230 bobwhites, and feathered an additional 385 bobwhites . Bobwhite density ranged from 0.6 to 7.6 bobwhites per ha (0.3 to 3.1 / acre) . Crippling loss ranged from 15 percent to 29 percent (x = 22 percent) of the total annual kill but did not correlate with fluctuations in bobwhite density.